Macropolitics of Nineteenth-Century Literature : Nationalism, Exoticism, Imperialism - Arac, Jonathan; Ritvo, Harriet (New Cultural Studies, 2016)
In contrast to the micropolitics of Foucault, macropolitics emphasizes that political transformations at the level of the state have great importance for many developments in nineteenth-century writing.